Spatial distribution of cannabinoid receptor type 1 (CB1) in normal canine central and peripheral nervous system. - Jessica Freundt-Revilla; Kristel Kegler; Wolfgang Baumgärtner; Andrea Tipold (PLoS ONE, 2017)
The endocannabinoid system is a regulatory pathway consisting of two main types of cannabinoid receptors (CB1 and CB2) and their endogenous ligands, the endocannabinoids. The CB1 receptor is highly expressed in the central and peripheral nervous systems (PNS) in mammalians and is involved in neuromodulatory functions. Since endocannabinoids were shown to be elevated in cerebrospinal fluid of epileptic dogs, knowledge about the species specific CB receptor expression in the nervous system is required. Therefore, we assessed the spatial distribution of CB1 receptors in the normal canine CNS and PNS. Immunohistochemistry of several regions of the brain, spinal cord and peripheral nerves from a healthy four-week-old puppy, three six-month-old dogs, and one ten-year-old dog revealed strong dot-like immunoreactivity in the neuropil of the cerebral cortex, Cornu Ammonis (CA) and dentate gyrus of the hippocampus, midbrain, cerebellum, medulla oblongata and grey matter of the spinal cord. Dense CB1 expression was found in fibres of the globus pallidus and substantia nigra surrounding immunonegative neurons. Astrocytes were constantly positive in all examined regions. CB1 labelled neurons and satellite cells of the dorsal root ganglia, and myelinating Schwann cells in the PNS. These results demonstrate for the first time the spatial distribution of CB1 receptors in the healthy canine CNS and PNS. These results can be used as a basis for further studies aiming to elucidate the physiological consequences of this particular anatomical and cellular distribution.